INDIGENOUS PEOPLE ENVIRONMENTAL RIGHTS VULNERABILITY TO CARBON TRADING MECHANISM: A LESSON LEARNED FOR INDONESIA - Azaria, Davilla Prawidya; Dirkareshza, Rianda; Nasution, Ali Imran (Universitas Bengkulu, 2023)
Developed countries are strictly obligated to reduce carbon emissions due to their industrial activities, contributing to a major concentration of greenhouse gases in the atmosphere. This paper aims to provide a basic overview of carbon reduction provisions under Kyoto Protocol and climate change frameworksdevelopment through the years. Practically in developing countries, its provision requires funding and transferring technology schemes by developed countries. The carbon markets emerged from Clean Development Mechanism (CDM) as a so-called eco-friendly project which potentially turns into a new form of capitalism in developing countries along with a tendency to depend on funding and transferring technology itself. Indigenous people are targeted groups directly affected by CDM projects and often neglect their fundamental rights. State is obligated to provide a forum for indigenous people to participate in the level of socializing, consultation, and law-making process of CDM as its nature being the most vulnerable group. Keywords: Carbon trade; climate change; environmental rights; indigenous people